АРХІТЕКТУРА ГРОМАДСЬКИХ БУДИНКІВ ТА КОМПЛЕКСІВ У УМОВАХ ДЕМОГРАФІЧНОГО ПЕРЕХОДУ - Шулдан Л. О. (World Science, 2019)
Trends in the development of public buildings’ architecture and complexes in the near future are determined, among other, by a demographic factor.It is suggested to conduct the analysis of the demographic situation on three levels: the macro level (global processes); the meso level (state) the micro level (region, city, village, etc.). The following indicators are determined at each level: the existing population; sections of age and gender groups; the proportion of rural and urban population. Which have been studied in the dynamics.Public buildings are most sensitive to demographic shifts. Thus, changes in public buildings’ structure would consist in: the growing role in the context of rapid urbanization; redistribution, development and appearance of their new types in accordance with the needs of a progressive cell (gerontological, educational, palliative, etc.) the predominance of modernization, expansion and renovation to new construction; providing polyfunctionality; maximum use of innovative arrangements and techniques.Presented analysis formed the basis for improving the energy efficiency of public buildings and complexes.